2004
DOI: 10.1091/mbc.e04-04-0352
|View full text |Cite
|
Sign up to set email alerts
|

Flagellar Radial Spokes Contain a Ca2+-stimulated Nucleoside Diphosphate Kinase

Abstract: The radial spokes are required for Ca 2؉ -initiated intraflagellar signaling, resulting in modulation of inner and outer arm dynein activity. However, the mechanochemical properties of this signaling pathway remain unknown. Here, we describe a novel nucleoside diphosphate kinase (NDK) from the Chlamydomonas flagellum. This protein (termed p61 or RSP23) consists of an N-terminal catalytic NDK domain followed by a repetitive region that includes three IQ motifs and a highly acidic C-terminal segment. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
106
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 56 publications
5
106
0
1
Order By: Relevance
“…These studies reveal that the C. reinhardtii radial spoke, which sediments as a 20S particle, contains at least 23 distinct polypeptides, termed radial spoke protein (RSP)1 to RSP23 Yang et al, 2001;Patel-King et al, 2004), with a combined molecular mass of approximately 1200 kDa (Padma et al, 2003). Five of these proteins are located in the spoke head and the rest are in the spoke stalk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies reveal that the C. reinhardtii radial spoke, which sediments as a 20S particle, contains at least 23 distinct polypeptides, termed radial spoke protein (RSP)1 to RSP23 Yang et al, 2001;Patel-King et al, 2004), with a combined molecular mass of approximately 1200 kDa (Padma et al, 2003). Five of these proteins are located in the spoke head and the rest are in the spoke stalk.…”
Section: Introductionmentioning
confidence: 99%
“…The human genes encoding these proteins are candidates for causing primary ciliary dyskinesia, a severe inherited disease involving missing or defective axonemal structures, including the radial spokes. 3,4,6,16 (HSP40),20 (calmodulin) Williams et al, 1989;Curry et al, 1992;Yang et al, 2005;Zimmer et al, 1988;King and Patel-King, 1995;Patel-King et al, 2004). The predicted amino acid sequences have provided hints as to the possible functions of these proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The first is the nm23-H7 class of nucleoside diphosphate kinase (NDK7) that consists of an N-terminal DM10 domain and two functional catalytic NDK modules. In Chlamydomonas, this protein (termed p40) is tightly associated with the flagellar axoneme and is solubilized only following treatment with 0.5 M KI [Patel-King et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…They are thought to be expressed predominantly in testis (Lacombe et al, 2000;Sadek et al, 2003) and NDK5, 8 (also named Sptrx-2; Sadek et al, 2001) and 9 (also named Txl-2; Sadek et al, 2003) are known to localize to the sperm flagella. An NDK5 homologue is identified in Chlamydomonas flagella, suggesting that it is a conserved flagellar protein (Patel-King et al, 2004). NDK8 and 9 are not conserved in lower organisms such as Chlamydomonas, but they are associated also with respiratory and lung cilia.…”
Section: Introductionmentioning
confidence: 99%
“…A first step to understanding the specific role of each NDK in cilia and flagella would be to clarify its expression and localization. However, while various NDP kinases have been reasonably well characterized, little information is available about NDK7 except that Patel- King et al (2004) surmised that this protein is tightly associated with the axoneme. They showed that Western blot analyses using an anti-Chlamydomonas NDK5 (p61) antibody detected an approximately 40 kDa axonemal protein (p40) in addition to NDK5 and, from its size, suggested that it might be Chlamydomonas NDK7.…”
Section: Introductionmentioning
confidence: 99%